Speech Perception in Noise Is Associated With Different Cognitive Abilities in Chinese-Speaking Older Adults With and Without Hearing Aids - Chen, Yuan; Wong, Lena L. N.; Chan, Shaina Shing; Yu, Joannie (Frontiers in Psychology, 2022)
Chinese-speaking older adults usually do not perceive a hearing problem until audiometric thresholds exceed 45 dB HL, and the audiometric thresholds of the average hearing-aid (HA) user often exceed 60 dB HL. The purpose of this study was to examine the relationships between cognitive and hearing functions (measured as audiometric or speech reception thresholds) in older Chinese adults with HAs and with untreated hearing loss (HL). Participants were 49 Chinese older adults who used HAs and had moderate to severe HL (HA group), and 46 older Chinese who had mild to moderately severe HL but did not use HAs (untreated; or UT group). Multiple linear regression analysis was employed to evaluate how well age, education level, audiometric thresholds, and speech perception in noise were related to performance on general cognitive function, working memory, executive function, attention, and verbal learning tests. Results showed that speech perception in noise alone accounted for 13%–24% of the variance in general cognitive function, working memory, and executive function in the UT group, and 9%–15% of the variance in general cognitive function and verbal learning in the HA group (i.e., medium effect sizes). Audiometric thresholds did not explain any proportion of the variance in cognitive functioning in the HA or UT group. Thus, speech perception in noise accounts for more variance in cognitive performance than audiometric thresholds, and is significantly associated with different cognitive functions in older Chinese adults with HAs and with untreated HL